PENETAPAN SESAN PADA PERNIKAHAN ADAT LAMPUNG PEPADUN - Ely Shintiya; Safira Maulana (STKIP Pesisir Selatan, 2025)
Objective: The sesan tradition is part of Lampung's traditional wedding ceremonies and is still preserved today, particularly in Negeri Ulangan Jaya Village, Negeri Katon District. This tradition is considered a form of respect for the principle of kinship in Lampung's traditional society. Sesan refers to the practice of the bride's family bringing various household items and furnishings to the groom's home prior to the wedding ceremony. These items are generally purchased using honest money previously given by the groom's family during the proposal, but they are also often obtained from contributions from the bride's relatives, so the total value of the sesan often exceeds the honest money itself. This study aims to examine in depth the meaning, concept, and purpose of the sesan tradition in Lampung's Pepadun traditional weddings, while also analyzing the factors influencing its size. With this approach, it is hoped that the philosophical and cultural values ​​embedded in this tradition can be understood and preserved. Specifically, this study aims to reveal the meaning of sesan, describe its implementation, explain its objectives, and identify various aspects that influence the determination of sesan values ​​in the context of Lampung Pepadun customs.